2002
DOI: 10.1108/03090560210417183
|View full text |Cite
|
Sign up to set email alerts
|

Discovering diversity in marketing practice

Abstract: Marketing practice varies among firms. However, the prescriptive literature emphasises a universal view of practice, a``one-size-fits-all'' view. This paper addresses the issue of explaining diversity in competitive space and over time. Diversity in competitive space reflects the existence of different routes to high performance. Diversity over time reflects some combination of change in the individual firm and change in a population of firms. In the former case, diversity is shaped by organisational change; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This would reaffirm suggestions by Loch () and Murray et al. () that there is no one best practice for NPD. However, there was a consensus on some characteristics as “best,” suggesting that there are likely generalizable characteristics of best and poor practice—those practices identified as poor should be avoided.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This would reaffirm suggestions by Loch () and Murray et al. () that there is no one best practice for NPD. However, there was a consensus on some characteristics as “best,” suggesting that there are likely generalizable characteristics of best and poor practice—those practices identified as poor should be avoided.…”
Section: Discussionsupporting
confidence: 81%
“…Some researchers contend that best practices vary from firm to firm, evolving over time, and with changes in the marketplace (Murray, O'Driscoll, and Torres, ). Thus, there is no “one best way” to high performance but rather different routes to the same end goal.…”
Section: The Meaning Of Npd Practice and Npd Best Practicementioning
confidence: 99%
“…Finally the maintainability of the CLIMB model, as well as for all maturity models, cannot be underestimated. Indeed, the concept of best practice is a dynamic concept (Griffin, 1997;Murray et al, 2002;Barczak and Kahn, 2012;Rossi, 2014): whatever is leading to extremely good results nowadays, could maybe lead to different results in the future. This is what happened for example with Cooper's stage and gate model, which is today considered not as extremely competitive as it was when it was introduced; but still it is entered in what we could call a must practice.…”
Section: Related and Future Researchmentioning
confidence: 99%
“…Jason Hobart, Marketing Director of Stirling Publisher; "...marketing is at the end of the day selling, and you sell more by having the right product at the right price and knowing who the right people are to sell it to." It can be argued then, that success is not just about basing business activity on a single, 'right' way (Murray et al 2002). Robbin's (1991) in-depth case study analysis of a family company, found that although strategic marketing planning was absent, the company was prospering.…”
Section: Article Of Faith: There Is Only One Definition Of Marketingmentioning
confidence: 99%